Effect of problem-based learning combined with seminar versus traditional teaching method in medical education in China: a systematic evaluation and meta-analysis - Wang, Haozhong; Yuan, Qiang; Guo, Yinling; Zheng, Xiuli; Luo, Jian; Qian, Junhui (Frontiers in Medicine, 2025)
ObjectivesThis study systematically evaluates the effectiveness of combining problem-based learning with the seminar teaching method and the traditional lecture-based learning model in medical education by meta-analysis.MethodsA computer-based search of major domestic and international literature databases was conducted, including PubMed, EMBASE, Web of Science Core Collection, Cochrane Library, China National Knowledge Infrastructure(CNKI), Wanfang Database, VIP Chinese Science and Technology Periodicals Database, and China Biology Medicine disk (CBMdisc). The search period spanned from the inception of the databases to 30 August 2024. Quantitative synthesis was performed using the RevMan V.5.4 software, following the Cochrane Reviewer’s Handbook guidelines and the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement.ResultsA total of 13 articles involving 857 medical students were included. The meta-analysis results revealed statistically significant differences between the experimental and control groups in the following areas: theoretical knowledge scores (MD = 4.99, 95% CI: 4.29–5.69, p < 0.00001); clinical skill scores (MD = 4.98,95% CI: 4.21–5.75, p < 0.00001); case analysis ability (SMD = 3.07, 95% CI: 2.66–3.47, p < 0.00001); Learning interest (SMD = 2.46, 95% CI: 1.89–3.03, p < 0.00001); Active learning (SMD = 3.26, 95% CI: 2.66–3.85, p < 0.00001); teamwork abilities (SMD = 1.66, 95% CI: 1.27–2.05, p < 0.00001); students’ research and academic ability (MD = 26.85, 95% CI: 24.79–28.91, p < 0.00001). The experimental group demonstrated superior outcomes in all areas compared to the control group.ConclusionThis meta-analysis showed that the integration of problem-based learning and seminar teaching methods is an effective method for improving theoretical knowledge scores, clinical skill scores, case analysis ability, learning interest, active learning, teamwork abilities and research and academic ability.